63 staff joined Kembara Lestari Merdeka to explore the beauty of nature - Siti Nur Azwin, Zulkapri (2020)
Pekan, 21 August 2020 - A total of 63 staff from Universiti Malaysia Pahang (UMP) walked three kilometres while waving the stripes of glory (jalur gemilang) as a way to express their love for the country in succeeding the Kembara Lestari Merdeka program organized by Registry recently.